GREM1/FGFR1-activated myofibroblasts induce immunosuppression and accelerate metastasis in high-grade serous ovarian cancer - Runrong Li; Xizhan Huang; Yue Chen; Xiaowen Chen; Yue Yang; Yurui Liu; Binyi Bai; Fanliang Meng; Yan Li; Yunshan Ning (Proceedings of the National Academy of Sciences, 2026)
Joint effect of cancer-associated fibroblasts (CAFs) and regulatory T cells (Tregs) can drive immunosuppression in high-grade serous ovarian cancer (HGSOC), thereby promoting tumor metastasis and limiting the clinical benefit of PD-1/PD-L1 blockade. However, the mechanistic crosstalk between CAFs and Tregs remains unclear. By integrating bulk RNA-seq, single-cell RNA-seq datasets, and spatial transcriptomics datasets with functional assays, we identified a population of TGF-β1-driven Gremlin1 (GREM1) + myofibroblastic CAFs (myCAFs) enriched in HGSOC metastatic lesions. These GREM1 + myCAFs activated the FGFR1-MAPKs-NFκB-TDO2-kynurenine axis via autocrine signaling, promoting tumor growth, metastasis, and immune evasion characterized by the infiltration of CD4 + Tregs and dysfunctional CD8 + T cells. GREM1 knockdown suppressed tumor metastasis, restored antitumor T cells response, remodeled CAF subtype composition and potentiated anti-PD-1 therapy efficacy. This study highlights the pro-metastatic role of GREM1 + myCAFs across multiple tumors and provides a rationale for combining anti-PD-1 therapy for metastatic HGSOC.